Cellular consequences of diminished protein O-Mannosyltransferase activity in baker’s yeast - Zatorska, Ewa; Schmitt, Jaro; Bausewein, Daniela; Strahl, Sabine (International journal of molecular sciences, 2017)
O-Mannosylation is a type of protein glycosylation initiated in the endoplasmic reticulum (ER) by the protein O-mannosyltransferase (PMT) family. Despite the vital role of O-mannosylation, its molecular functions and regulation are not fully characterized. To further explore the cellular impact of protein O-mannosylation, we performed a genome-wide screen to identify Saccharomyces cerevisiae mutants with increased sensitivity towards the PMT-specific inhibitor compound R3A-5a. We identified the cell wall and the ER as the cell compartments affected most upon PMT inhibition. Especially mutants with defects in N-glycosylation, biosynthesis of glycosylphosphatidylinositol-anchored proteins and cell wall β-1,6-glucan showed impaired growth when O-mannosylation became limiting. Signaling pathways that counteract cell wall defects and unbalanced ER homeostasis, namely the cell wall integrity pathway and the unfolded protein response, were highly crucial for the cell growth. Moreover, among the most affected mutants, we identified Ost3, one of two homologous subunits of the oligosaccharyltransferase complexes involved in N-glycosylation, suggesting a functional link between the two pathways. Indeed, we identified Pmt2 as a substrate for Ost3 suggesting that the reduced function of Pmt2 in the absence of N-glycosylation promoted sensitivity to the drug. Interestingly, even though S. cerevisiae Pmt1 and Pmt2 proteins are highly similar on the sequence, as well as the structural level and act as a complex, we identified only Pmt2, but not Pmt1, as an Ost3-specific substrate protein.